Alytaus miesto periodinė spauda 1920-1940 metais - Šimkevičius, Šarūnas (Knygotyra, 2002)
The first newspapers in Alytus were produced in a manuscript form. This kind of publications was popular among students after the World War l. Alytus was not an exception. The bulk of periodicals in this town was published by Lithuanian Christian Democratic Party local organisations. The first town's newspaper printed by the printing house in Kaunas was "Dzūkų bizūnas" (A dzūkai whip) published in 1925-1926. In the 20s the first town's printing house was established. Some of the creators of the periodical press acquired publishing experience before arriving to Alytus, however, it was not sufficient to develop the press in town successfully. During the 20s censorship also influenced the press negatively. During 30s the local community was not capable of supporting the most serious newspaper "Alytaus dzyvai" (Alytus wonders) (1931-1932). There was a lack of understanding of the significance of a publication, besides the local community was less financially and culturally empowered in comparison to Samogitian or Suvalkija town communities. However, the creation of newspapers in general was a significant fact and indicated that Alytus was growing into a significant town and the community was maturing.